Three new species of Russulaceae from India based on morphology and molecular phylogeny - Latha, K. P. Deepna; Raj, K. N. Anil; Farook, V. Adnaan; Sharafudheen, Shahina A.; Parambil, Neeraja K.; Manimohan, Patinjareveettil (Phytotaxa, 2016)
Three new species of Russulaceae, Lactifluus umbonatus and Lactifluus indicus belonging to Lf. subg. Gerardii and Lactarius keralensis belonging to L. subg. Piperites, are described from Kerala State, India. Comprehensive descriptions, photographs, line drawings and comparisons with phenetically similar and phylogenetically related species are given. Nuclear ribosomal internal transcribed spacer regions (ITS) of the three species were sequenced and analyzed. In addition, nuclear ribosomal large subunit (nLSU) gene of Lactifluus indicus was sequenced and the sequence was used in BLASTn search to find similar sequences. Maximum likelihood (ML) analysis based on the ITS sequences confirmed both the novelty of these species and their placement within their respective genera. The discovery of Lactifluus umbonatus and Lf. indicus represent the first report of novel species belonging to Lf. subg. Gerardii from India. Lactifluus indicus represents the second record of a pleurotoid Lactifluus species from India.